Study on landing control method based on incremental dynamic inverse - DUAN Zhuoyi; ZHAO Letian; ZHANG Junhong; LIU Xiaoxiong (Hangkong gongcheng jinzhan)
Accurate landing control and improving the safety and reliability of the landing process are difficult issues in the safe recovery of carrier based aircraft. A landing control system based on incremental dynamic inverse is proposed. The method of an angle of attack maintenance loop and a trajectory rate control loop based on incremental dynamic inversion is used，which can achieve decoupling of angle of attack and trajectory，as well as direct control of trajectory by direct lift. A differential tracker is introduced to estimate the track angular acceleration signal required in the incremental dynamic inverse control law. The landing control system is verified with simulation. The results show that the designed landing control system based on incremental dynamic inverse has excellent control accuracy，speed，and robustness. It can achieve accurate tracking of the trajectory under different sea conditions interference，and the landing points can meet the quality requirements for the distribution of carrier based aircraft landing points.